Local television viewing in Western Flemingsberg 1981 - Hedman, Lowe (Uppsala University, 1985)
This study was made on the request of the Local Radio Committee to map the extent of looking at local television broadcasts and which groups are looking. The inhabitants of Västra Flemingsberg was asked questions about their knowledge of local television broadcasting and their attitude towards it. Since the broadcastings are made by local organizations they were also asked about their affiliations with those and other organizations. To create a standard of the respondents´ general mass media activity there were questions about their viewing on national television, listening to national radio and newspaper-reading. The background-variables were sex, age, living conditions, work situation, nationality and language.

This study was made on the request of the Local Radio Committee to map the extent of looking at local television broadcasts and which groups are looking. The inhabitants of Västra Flemingsberg was asked questions about their knowledge of local television broadcasting and their attitude towards it. Since the broadcastings are made by local organizations they were also asked about their affiliations with those and other organizations. To create a standard of the respondents´ general mass media activity there were questions about their viewing on national television, listening to national radio and newspaper-reading. The background-variables were sex, age, living conditions, work situation, nationality and language.
Tittandet på när-TV i Västra Flemingsberg 1981
Keywords: Media; Media; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap